Bicuspid aortic valve-associated aortopathy: Where do we stand?. (August 2019) - Messner, Barbara; Bernhard, David
Abstract: Herein we summarize the current knowledge on the bicuspid aortic valve (BAV)-associated aortopathy regarding clinical presentation and disease sub-classification, genetic background, hemodynamics, histopathology, cells and signaling, animal models, and biomarkers. Despite enormous efforts in research in all of the above areas, important issues remain unknown: (i) what is the ontogenetic basis of BAV development? (ii) how can we explain the diversity of BAV and associated aortopathy phenotypes? (iii) what are the signaling processes in aortopathy pathogenesis and how can we interfere with these processes? Despite undoubtedly great progress that has been made in the understanding of BAV-associated aortopathy, so far researchers have put together a heap of Lego bricks, but at present it is unclear if the bricks are compatible, how they fit together, and which parts are missing to build the true model of the BAV aorta. A joint approach is needed to accelerate research progress.